Learn to draw Disney classic characters. (Walter Foster Jr., 2020)
"Learn to Draw Disney Classic Characters includes drawing projects for characters from Mickey Mouse & Friends, Winnie the Pooh, The Lion King, Toy Story, and more. The easy-to-follow instructions in this book will guide you through the process of drawing your favorite classic Disney characters. You just need to grab a pencil, a piece of paper, and your copy of Learn to Draw Disney Classic Characters, and flip to the character you want to draw. Plus, learn some fun facts about these classic Disney characters as you learn to draw them. Brief character descriptions and art instruction from professional Disney animators round out this exciting artistic adventure"--
Mickey Mouse -- Minnie Mouse -- Pluto -- Goofy -- Donald Duck -- Winnie the Pooh -- Tigger -- Piglet -- Eeyore -- Simba -- Mufasa -- Scar -- Woody -- Buzz Lightyear.
Ages 6-8
Grades 2-3
Keywords: Cartoon characters -- Juvenile literature; Disney characters -- Juvenile literature; Drawing -- Technique -- Juvenile literature